2011
DOI: 10.1186/1471-2164-12-293
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq: technical variability and sampling

Abstract: BackgroundRNA-seq is revolutionizing the way we study transcriptomes. mRNA can be surveyed without prior knowledge of gene transcripts. Alternative splicing of transcript isoforms and the identification of previously unknown exons are being reported. Initial reports of differences in exon usage, and splicing between samples as well as quantitative differences among samples are beginning to surface. Biological variation has been reported to be larger than technical variation. In addition, technical variation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(229 citation statements)
references
References 38 publications
8
218
0
3
Order By: Relevance
“…In similar studies of pigs (Chen et al, 2011;Esteve-Codina et al, 2011) and cattle (Huang et al, 2012), in which 61.6-77.8% of reads were matched to the reference genome, our results were comparable for sheep. The percentage of reads mapped to the reference genes were lower than that mapped to the O. aries genome, a result potentially due to the GC content, type of cells, and other reasons (McIntyre et al, 2011;Sendler et al, 2011). The percentage of reads mapped to the reference genes in the LCL libraries (59.91, 56.89, and 56.09%) were slightly higher than those for the MCL libraries (55.03, 56.44, and 54.87%), but the percentage of reads mapped to the O. aries genome were not similar.…”
Section: Discussionmentioning
confidence: 98%
“…In similar studies of pigs (Chen et al, 2011;Esteve-Codina et al, 2011) and cattle (Huang et al, 2012), in which 61.6-77.8% of reads were matched to the reference genome, our results were comparable for sheep. The percentage of reads mapped to the reference genes were lower than that mapped to the O. aries genome, a result potentially due to the GC content, type of cells, and other reasons (McIntyre et al, 2011;Sendler et al, 2011). The percentage of reads mapped to the reference genes in the LCL libraries (59.91, 56.89, and 56.09%) were slightly higher than those for the MCL libraries (55.03, 56.44, and 54.87%), but the percentage of reads mapped to the O. aries genome were not similar.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that no clear correlation of targeting efficiency was found either with the extent of complementarity between artificial miRNAs and targets or with expression levels of targets 55 . In addition, RNA-seq technique has been shown recently with technical variability particularly in exons at low levels of read coverage, and the relative abundance of a transcript can also substantially disagree 56 . Besides, plant intrinsic variations might contribute to the variations in miRNA expressions, which exhibited as opposite or subtle expression changes compared with the majority, particularly in response to low levels of environmental changes, that is, 26 o C temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Illumina sequencing produces negligible technical variability, removing the need for technical replication in RNAseq experiments (Marioni et al, 2008). However, when coverage is low for certain transcripts, technical variation can still arise (McIntyre et al, 2011). Thus, technical replication should be considered for dual RNA-seq experiments where there is low representation of pathogen RNA within a sample, resulting in low coverage of pathogen transcripts.…”
Section: Sample Replicationmentioning
confidence: 99%